A 36-Hour Unplugged Full-Scale Exercise: Closing the Gaps in Interagency Collaboration between the Disaster Medical Assistance Team and Urban Search and Rescue Team in Disaster Preparedness in Taiwan - Foo, Ning-Ping (Emerg Med Int, 2021)
INTRODUCTION: Disaster medical assistance team (DMAT) and urban search and rescue team (USAR) need to cooperate seamlessly to save lives in disasters, but related research is limited. OBJECTIVES: To estimate the disaster preparedness of the DMAT and the barriers affecting interagency cooperation between the DMAT and the USAR team. METHODS: This was an observational study of a full-scale exercise conducted in Taiwan from November 16 to 18, 2018. The exercise scenario simulated a magnitude 7 earthquake in Tainan City. DMATs from other counties were deployed and cooperated with local USAR teams to carry out disaster relief. Our study invited 7 experts to evaluate DMATs on disaster preparedness capabilities and the interagency collaboration between DMATs and USAR. RESULTS: A total of eight DMATs, consisting of 30 physicians, 65 nurses, 74 logisticians, 5 health bureau personnel, and 85 USAR teams, participated in this exercise. During the mission, 176 patients were treated. The capabilities of each team were generally consistent with the basic technical standards for type I emergency medical teams, but the compliance rates for basic local anesthesia, cold chain equipment for medication, rapid blood test tools, and sterilization devices were only 50%, 12.5%, 12.5%, and 9%, respectively. In addition, 53% of participants reported abnormal vital signs, indicating that it was a high-stress situation. Moreover, the main barriers to interagency collaboration were differing perspectives and poor mutual understanding. CONCLUSION: A full-scale exercise carried out jointly with DMATs and USAR teams was valuable for disaster preparedness, particularly in terms of understanding the weaknesses of those teams and the barriers to interagency collaboration.